CHALLENGES IN PRESERVING THE WORLD HERITAGE EARTHEN SITE OF CHAN CHAN, IN PERU - Correia, Mariana (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
Chan Chan is an archaeological site in Trujillo, on the north coast of Peru. The archaeological complex is the largest earthen site in the world and has been on the World Heritage in Danger list since being inscribed in 1986, following its classiication as a UNESCO World Heritage site. The aim of this paper is to address the state of the art, regarding the challenges and the current preservation status, and to understand why the site has been on the list for last 25 years. This paper also discusses the architectural and archaeological signiicance of Chan Chan, its assessment as a World Heritage site, the management-plan development, the conservation state of the site, the conservation practice on site, the conservation philosophy, reasons for conservation failure, key issues emerging from qualitative analysis, and inally, in conclusion, recommendations to consider.